The role of digitalization in early internationalization Research : A systematic literature review and future research directions - Appiah, Emmanuel Kusi; Gabrielsson, Peter; Rialp Criado, Alex (Elsevier, 2024)
The purpose of this research is to systematically collate and synthesize the literature on how digitalization-related antecedents influence the processes and outcomes of early internationalizing firms. To do so, the present study systematically reviews a total of 120 related articles published in a broad range of academic journals from 1994 to 2024. The review enables us to outline the development of major research areas in terms of themes, theoretical approaches, and methodological issues at the intersection of the early internationalization and digitalization research. We contribute by offering a model that delineates a more subsumed, multilevel explanation of the interface of early internationalization and digitalization. Further, we propose a number of future research directions based on the integration of the reviewed articles and inputs purposefully collected from surveyed scholars in the field.
Keywords: Early internationalization; Digitalization; Born global; International new venture; digital technology; fi=Kansainvälinen liiketoiminta|en=International Business|